Analisis Level Risiko Bahaya Pada Usaha Pencucian Mobil dengan Metode AS/NZS 4360:2004 - Deny Poniman Kosasih; A. Moeslihat Komara; Hari Din Nugraha; Cecep As Sidik (FAKULTAS TEKNIK UNIVERSITAS SUBANG, 2020)
Over time, the number of motorized vehicles has increased significantly, this is in line with the need for vehicle maintenance, namely vehicle washing, especially cars. But on the other hand, there is a risk of danger that occurs in the car wash process. This study aims to identify potential hazards in the work process at a car wash. The type of survey research, the method of the assessment process refers to the Australian/New Zealand standard (AS/NZS 4360:2004). The results showed the highest level of risk in the car washing process at Car Wash